Meningkatan Literasi Keuangan Pada Masyarakat Desa Kebanggan Kecamatan Moga Melalui Program Literasi Bank Syariah - Nafiyah, Ilma; Maulidya, Afikoh; Rosyada, Naila; Putri, Elviana Komala; Lestari, Elsa; Adinugraha, Hendri Hermawan (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2023)
The financial industry is currently innovating rapidly, it can be seen from the various services provided by financial institutions that have advantages and disadvantages that are sometimes not understood by the public. Currently, apart from providing conventional financial institutions, financial institutions also provide Islamic financial institutions. The difference between the two financial institutions lies in the sharia-based and conventional-based management. One of the sharia financial institutions that is growing rapidly is sharia banking. Public understanding of various contracts in Islamic banking needs to be clarified by providing easy-to-understand examples for the community, both from the upper and lower levels of society. The low literacy of Islamic financial institutions in Moga sub-district, precisely in Kebanggan Village, is caused by their low level of education. The existence of this service is expected to provide understanding to jamiyah mothers and can improve literacy skills. The method used is direct mentoring with a lecture approach. From this assistance, it is hoped that the people of Kebanggan Village, Moga District, can better understand the various types of Islamic financial institutions in Indonesia, the principles of Islamic finance, the differences between Islamic banks and conventional banks, as well as the products and services offered by Islamic banks, such as mudharabah products.